2023
DOI: 10.3390/su15097397
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship between Supply and Demand of Ecosystem Services and the Influencing Factors in Resource-Based Cities in China

Abstract: Exploring the coupling coordination degree between supply and demand and its key influencing factors is important for ecological security and socioeconomic sustainable development in resource-based cities. On the basis of measuring the supply and demand of ecosystem services in 125 resource-based cities in China from 2000 to 2020, we analyzed the matching pattern and coupling coordination degree between supply and demand. The Spearman correlation analysis and quantile regression models were used to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Delphin et al [43] found that climate change had a more significant impact on water supply and service supply than other driving factors in two watersheds in Florida, USA. Zhao et al [44] noted that population had the greatest impact on water supply service demand in Gansu province of China. We selected factors such as elevation, slope, soil layer thickness, rainfall, temperature, NDVI, land use type, population density, and GDP to evaluate the impact of these factors on the ratio of water supply and service demand.…”
Section: Factors Influencing the Supply And Demand Patterns Of Water ...mentioning
confidence: 99%
“…Delphin et al [43] found that climate change had a more significant impact on water supply and service supply than other driving factors in two watersheds in Florida, USA. Zhao et al [44] noted that population had the greatest impact on water supply service demand in Gansu province of China. We selected factors such as elevation, slope, soil layer thickness, rainfall, temperature, NDVI, land use type, population density, and GDP to evaluate the impact of these factors on the ratio of water supply and service demand.…”
Section: Factors Influencing the Supply And Demand Patterns Of Water ...mentioning
confidence: 99%
“…However, these studies have frequently ignored potential spatial correlations and complex interdependencies among multiple ESs. Therefore, the present study conducted a quantitative analysis to examine the relationship between ecosystem supply and demand and their evolution to reveal the spatiotemporal heterogeneity of ecosystem service provision in the study area [21][22][23]. The spatiotemporal reoccurrence of ESs forms bundles known as ecological service bundles, and these bundles allow the quantitative study of ESs.…”
Section: Introductionmentioning
confidence: 99%
“…Supply and demand reflect the flow of ecosystem services through ecosystems and human social systems. The relationship between the supply of and demand for ecosystem services can effectively reflect the state of regional economic development and the state of the ecological environment [13]. On the one hand, the amount of ecological products and services that water ecosystems can provide is no longer able to meet the increasing demand needed for human society to develop, and on the other hand, human society's investment in water ecology is not enough to support the restoration of water ecosystems' ability to supply goods [14][15][16].…”
Section: Introductionmentioning
confidence: 99%